y = 3Cosx + 2Sin²x - 1
Найдём производную :
y' = (Cosx)' + 2(Sin²x)' - 1' = - 3Sinx + 4SinxCosx
Приравняем производную к нулю :
- 3Sinx + 4SinxCosx = 0
Sinx(- 3 + 4Cosx) = 0
Sinx = 0
- 3 + 4Cosx = 0
Cosx = 0,75
Если Sinx = 0 , то Cosx = ± 1
1) Sinx = 0 ⇒ Cosx = - 1 ⇒
y = 3 * (- 1) + 2 * 0 - 1 = - 4 - наименьшее
2) Sinx = 0 ⇒ Cosx = 1 ⇒
y = 3 * 1 + 2 * 0 - 1 = 2
3) Cosx = 0,75 ⇒ Sin²x = 1 - Cos²x = 1 - 0,75² = 1 - 0,5625 = 0,4375
y = 3 * 0,75 + 2 * 0,4375 - 1 = 2,25 + 0,875 - 1 = 2,125 - наибольшее
ответ : наименьшее - 4 , наибольшее 2,125
(-1,5;2,5) (2;-1) (-2;1) (1,5;-2,5)
Объяснение:
{x²+2xy+y²=1 {(x+y)²=1 {x+y=-1 {x+y=1
{x²-xy=6 ⇔ {x²-xy=6 ⇔ {x²-xy=6 ⇔ {x²-xy=6
{y=-1-x { y=1-x
{x²-x(-1-x)=6 {x²-x(1-x)=6
x²+x+x²-6=0 x²-x+x²-6=0
2x²+x-6=0 2x²-x-6=0
D=1²-4·2·(-6)=49 D=(-1)²-4·2·(-6)=49
x₁=(-1-7)/4=-2 y₁=-1-(-2)=1 x₁=(1-7)/4=-1,5 y₁=1-(-1,5)=2,5
x₂=(-1+7)/4=1,5 y₂=-1-1,5=-2,5 x₂=(1+7)/4=2 y₂=1-2=-1